Historical traditions and cultural and economic tenability of the modern landscape design of the Residence of Bukovinian and Dalmatian Metropolitans - Korotun, Iryna; Balaniuk, Yuliana; Vakolyuk, Anatolii (Landscape Architecture and Art, 2021)
The article is devoted to the analysis of the history of creation of the Residence of Bukovinian and Dalmatian Metropolitans in the city of Chernivtsi, where the Yurii Fedkovych Chernivtsi National University is now located. A part of this ensemble is a park, the uniqueness of which is due to the combination of three types of parks at the same time – the Italian garden, the French regular park and the English landscape park. The periods of creation of the park, participation of landscape designers and clergymen are covered in detail, landscape techniques and their correspondence to the three above-mentioned types of parks are analyzed. The range of problems of the park’s existence and measures for its arrangement are described. Proposals for the creation of a unique Bible garden with the symbolic meaning of landscape sceneries are described separately. The proposed measures are substantiated in terms of creating a new tourist attraction.